Peran Cognitive Behavioral Therapy (CBT) dalam Menurunkan Pola Fear-avoidance pada Pasien Pasca Operasi - Raychana Robbi Rodhiyah (Psikologi UHAMKA, 2026)
Pain-related fear that develops into a fear-avoidance pattern is known to contribute to delays in the post-operative rehabilitation process. However, studies exploring the psychological dynamics of pain-related fear and fear-avoidance patterns in elderly patients in real clinical contexts, particularly through a case study approach integrating qualitative and quantitative data, are still limited. This case study aims to examine the dynamics of pain-related fear with fear-avoidance patterns as well as the role of Cognitive Behavioral Therapy (CBT) interventions in supporting the recovery process. The approach used is mixed methods with a single-case A–B design on a 70-year-old female patient post-surgery. Data were collected through semi-structured clinical interviews, direct observation, and psychological scales (HADS, NRS, FABQ). Quantitative analysis was conducted descriptively by comparing scores in the baseline phase (A) and post-intervention (B), while qualitative data were analyzed thematically. Data integration was conducted through method triangulation. The results showed that in the baseline phase there was moderate anxiety (HADS = 14), high pain intensity (NRS = 9 during movement), as well as high fear-avoidance beliefs (FABQ = 23). After the CBT intervention, there was a decrease in anxiety (HADS = 6), a decrease in pain perception (NRS = 5), and a reduction in fear and tension toward pain. Qualitatively, the subject showed a change in beliefs toward being more adaptive and an increase in participation in rehabilitation activities. These findings indicate that fear-avoidance beliefs act as a key mechanism maintaining recovery barriers, and confirm that CBT intervention is effective in reducing pain-related fear and increasing patient participation in post-operative rehabilitation.